(untitled) (Journal of Fiber Bioengineering and Informatics, 2015)
The basic theory of camera calibration is firstly introduced in this paper. The model of camera distortion is put forward. And discussed the parameters and the calibration process of the mathematical model of 3D human body reconstruction. In the process of camera calibration, an improved algorithm based on the two steps is proposed. This method has low requirements on experimental. This method has low requirement to experiment, and only with coplanar points to calibrate. By the process of fractional step calibration, the nonlinear equation is linear, which is beneficial to improve the calibration accuracy.